Language, gender and identity - Perović, Slavica (Javnost (Ljubljana), 2012)
In this paper we shall deal with the interdependence of gender and language on the one hand and gender and identity on the other. The relevant framework of analysis will encompass the theory of dominance, the theory of difference and performativeness theory. The current situation in Montenegro regarding the subject matter of our investigation somewhat reflects the chronology of the research in these categories and the historical order of their appearance. There is strong evidence to support the main postulates of the theory of dominance (Lakoff 1974) primarily expressed in terms of the markedness of the female member contrasted with the unmarkedness of the male. Also, the gender non-parallelism present in the public and private spheres finds fertile soil in the Montenegrin mentality, behaviour and overall cultural script of pronounced patriarchality. Perhaps the theory of difference would be nominally the best theory to describe the gender situation in Montenegro in both its aspects: difference as unintentional dominance (Tannen 1990) and "different" in the meaning of "worse" when applied to women. At the same time,performativeness theory (Butler 1990, 1997), which takes the stand that gender means acting and doing, not just being, would be very suitable for grasping the various manifestations of gender identity. All the while, irrespective of these theories, the media exert their inexorable influence in maintaining the traditional role of the woman (and men), albeit with some new vocabulary.
Keywords: spol; spolna diferenciacija; enakost spolov; gender equality; jezikovne pravice; izražanje